2018
DOI: 10.1155/2018/1898671
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Hemodialysis on Thiol-Disulphide Homeostasis in Critically Ill Pediatric Patients with Acute Kidney Injury

Abstract: Aim To evaluate thiol/disulphide homeostasis as a new indicator of oxidative stress in AKI patients and to determine the effect of HD on antioxidant balance and oxidative stress through plasma thiols. Methods This study was performed in patients aged between 12 months and 18 years prospectively who underwent hemodialysis due to AKI and were followed up for a year in a 22-bed tertiary pediatric intensive care unit. 20 patients and 39 controls were included. Results No difference was present between the groups i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
9
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 34 publications
1
9
0
1
Order By: Relevance
“…Previous research demonstrated that patients with hospital-acquired AKI had lower levels of unadjusted plasma-free thiols as compared to critically ill patients without AKI and healthy subjects [ 30 ]. In another study, pediatric patients with AKI had lower levels of unadjusted plasma-free thiols as compared to healthy controls [ 31 ]. Both the unadjusted thiol levels correlated with the albumin-adjusted thiol levels in our study; in contrast, we used adjusted thiol levels to correct for the albumin levels.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous research demonstrated that patients with hospital-acquired AKI had lower levels of unadjusted plasma-free thiols as compared to critically ill patients without AKI and healthy subjects [ 30 ]. In another study, pediatric patients with AKI had lower levels of unadjusted plasma-free thiols as compared to healthy controls [ 31 ]. Both the unadjusted thiol levels correlated with the albumin-adjusted thiol levels in our study; in contrast, we used adjusted thiol levels to correct for the albumin levels.…”
Section: Discussionmentioning
confidence: 99%
“…To date, to the best of our knowledge, no other study unravelled the association between (albumin-adjusted) plasma-free thiols and AKI in patients in the ICU with and without sepsis. Previous studies demonstrated lowered plasma-free thiol levels in children with AKI [ 31 ] or adult patients with AKI [ 30 ], although not among adult patients in the ICU. Moreover, as thiols are influenced by serum albumin levels, which might be affected by critical illness or sepsis, we corrected the thiol levels for albumin, in contrast to previous studies.…”
Section: Discussionmentioning
confidence: 99%
“…Although it has been shown that thiols play a role in the pathogenesis of many disease, such as ankylosing spondylitis, lung cancer, rheumatoid arthritis, diabetic nephropathy, sickle cell disease, gastric cancer, and juvenile idiopathic arthritis [15][16][17][18][19][20][21], few studies have been conducted with respect to sepsis [22,23].…”
Section: Discussionmentioning
confidence: 99%
“…Ayar G et al measured thiol-disulphide homeostasis as oxidative stress marker in critically ill children with sepsis [23]. They found that the levels of native thiol, total thiol, and disulphide were significantly decreased in patients with septis shock and sepsis.…”
Section: Discussionmentioning
confidence: 99%
“…Previous research demonstrated that patients with hospital-acquired AKI had lower levels of unadjusted plasma free thiols as compared to critically ill patients without AKI and healthy subjects (30). In another study, paediatric patients with AKI also had lower levels of unadjusted plasma free thiols as compared to healthy controls (31).…”
Section: Discussionmentioning
confidence: 91%